2022
DOI: 10.21608/tsnj.2022.221573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program for Nurses on Clinical Outcomes of Cancer patients with Metastatic Spinal Cord Compression

Abstract: Background: Spinal cord compression is a common oncological emergency that requires early detection and prompt treatment as it can result in permanent neurological deficit. Nurses are often involved in supporting patients living with cancer. They may be the first healthcare professional to recognize the "red flag" symptoms of MSCC. Early recognition by the nurses will prompt timely investigation, treatment and potentially reduce the risks of patient's having a permanent disability. Aim: To determine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…from investigator's point of view, this result may be due to that the majority of nurses were recently graduated and didn't attend training courses related to care of patient with SCI. This is consistent with Khalil et al (22) whose study revealed that most of the studied nurses had low level of knowledge regarding care for patients with SCI.…”
Section: Discussionsupporting
confidence: 91%
“…from investigator's point of view, this result may be due to that the majority of nurses were recently graduated and didn't attend training courses related to care of patient with SCI. This is consistent with Khalil et al (22) whose study revealed that most of the studied nurses had low level of knowledge regarding care for patients with SCI.…”
Section: Discussionsupporting
confidence: 91%